Tales of power - Castaneda, Carlos 1931-1998 (Arkana/Penguin Books, 1990)
In this work, Carlos Castaneda at completes the long journey into the world of sorcery that began with his now-legendary meeting with don Juan. Until now don Juan has performed his acts of power in his world, the dry, barren deserts and mesas of his birth. Now, in an unexpected encounter, don Juan appears in Castaneda's modern urban world, at ease in a well-tailored suit, demonstrating his lessons of power in the crowded, busy streets, using the city scene, as he uses everything, to unfold the wings of Carlos Castaneda's perception. Thus, Don Juan concludes the instruction of Castaneda with his most powerful and mysterious lesson in the sorcerer's art--a dazzling series of visions that are at once an initiation and a deeply moving farewell.